Evolution of Late Paleozoic Magmatic Arc in the Yili Block, NW China: Implications for Oroclinal Bending in the Western Central Asian Orogenic Belt. Issue 12 (10th December 2020) - Wang, Xiangsong; Cai, Keda; Sun, Min; Zhao, Guochun; Xiao, Wenjiao; Xia, Xiaoping
Abstract: Subduction transformation (advancing vs. retreating) may be manifested by compositional variations of arc magmas and may result in oroclinal bending. Identifying relevant chemical and physical processes is crucial for understanding accretionary orogenesis and continental crustal evolution. The Northern Yili Block (NYB) was situated on an active margin associated with subduction of the Junggar Ocean (part of the Paleo‐Asian Ocean) and underwent perplexing accretionary orogenesis in late Paleozoic. Two episodes of subduction‐related granitoid magmatism have been identified, the first in the Late Devonian (374–369 Ma) and the second in the Late Carboniferous (ca. 304 Ma). These two episodes of granitoid magmatism exhibit contrasting features; for example, the first episode shows low εNd (t) (−6 to −2) and εHf (t) (−12 to +3) values, while the second episode displays relatively higher values (−2 to +7 and 0 to +20, respectively), suggesting increase contribution of juvenile components in the magma sources. The calculated zircon saturation temperatures are mostly <800°C for the first episode but increased to >800°C for the second episode. The (La/Yb)N ratios of the two‐episode granitoids vary from 2–17 to 1–9, indicative of the NYB crustal thinning in the Late Carboniferous. In addition, the migrations of the magmatic arc and trench in the NYB took place coevally in the Late Carboniferous and were accompanied by development of an accretionary complex and an immature back‐arc basin. We interpret that the arc magmatic variations and migrations reflect geodynamic transition from the Late Devonian advancing subduction to the Late Carboniferous retreating subduction. The retreating subduction of the Junggar oceanic plate possibly resulted in prominent oroclinal bending of the southern Kazakhstan collage system in the Late Carboniferous. Key Points: Two episodes of granitoids were derived from mixed sources of the Proterozoic basement and various Paleozoic juvenile materials The tectonic transformation occurred in the Northern Yili Block from advancing to retreating subduction in late Paleozoic The subduction zone transition may account for oroclinal bending in southern limb of the Kazakhstan Orocline in the Late Carboniferous